Anthropometric factors and ovarian cancer risk: A systematic review and nonlinear dose‐response meta‐analysis of prospective studies. Issue 8 (24th September 2014) - Aune, Dagfinn; Navarro Rosenblatt, Deborah A.; Chan, Doris Sau Man; Abar, Leila; Vingeliene, Snieguole; Vieira, Ana Rita; Greenwood, Darren C.; Norat, Teresa
<x xml:space="preserve">Abstract</x> In the World Cancer Research Fund/American Institute for Cancer Research report from 2007 the evidence relating body fatness to ovarian cancer risk was considered inconclusive, while the evidence supported a probably causal relationship between adult attained height and increased risk. Several additional cohort studies have since been published, and therefore we conducted an updated meta‐analysis of the evidence as part of the Continuous Update Project. We searched PubMed and several other databases up to 20th of August 2014. Summary relative risks (RRs) were calculated using a random effects model. The summary relative risk for a 5‐U increment in BMI was 1.07 (95% CI: 1.03–1.11, I2 = 54%, n = 28 studies). There was evidence of a nonlinear association, pnonlinearity < 0.0001, with risk increasing significantly from BMI∼28 and above. The summary RR per 5 U increase in BMI in early adulthood was 1.12 (95% CI: 1.05–1.20, I2 = 0%, pheterogeneity= 0.54, n = 6), per 5 kg increase in body weight was 1.03 (95% CI: 1.02–1.05, I2 = 0%, n = 4) and per 10 cm increase in waist circumference was 1.06 (95% CI: 1.00–1.12, I2 = 0%, n = 6). No association was found for weight gain, hip circumference or waist‐to‐hip ratio. The summary RR per 10 cm increase in height was 1.16 (95% CI: 1.11–1.21, I2 = 32%, n = 16). In conclusion, greater body fatness as measured by body mass index and weight are positively associated risk of ovarian cancer, and in addition, greater height is associated with increased risk. Further studies are needed to clarify whether abdominal fatness and weight gain is associated with risk.